Apuntes para la reconstrucción de las relaciones inter- y multidisciplinares desde la lingüística en la Edad Media - González Jiménez, Juan Miguel (Pontificia Universidad Católica del Perú, 2025)
In this research, we analyze the contributions of medieval authors, both Christian and Islamic, with the aim of exploring the inter- and multidisciplinary relationships between linguistics and the biological and behavioral sciences in their texts. Methodologically, we employ the Theory of Textual Series and the Theory of the Canon, through which we adopt a macro-structural, dialogical and dynamic perspective, which can be found in the interaction among primary sources. The results show that the texts of Augustine of Hippo, Averroes and Thomas Aquinas tangentially develop some of the interests of biolinguistics, neurolinguistics and psycholinguistics nowadays; in particular, they focus on language versus animal communication systems, linguistic acquisition and the relationship between mind and brain/heart.

En este artículo se analizan las aportaciones de autores medievales, tanto cristianos como islámicos, con el objetivo de indagar en las relaciones inter- y multidisciplinares entre la lingüística y las ciencias biológicas y del comportamiento en sus textos. Metodológicamente, nos valemos de las teorías de las series textuales y del canon, mediante las que adoptamos una perspectiva macroestructural, dialógica y dinámica presente en la interacción entre las fuentes primarias. Los resultados demuestran que los textos de Agustín de Hipona, Averroes y Tomás de Aquino desarrollan tangencialmente algunos de los intereses de las actuales biolingüística, neurolingüística y psicolingüística; en concreto, el lenguaje frente a los sistemas de comunicación animal, la adquisición lingüística y la relación entre mente y cerebro/corazón.
Notes for the Reconstruction of Inter- and Multidisciplinary Relations in Linguistics in the Middle Ages
Keywords: Linguistic historiography; Inter- and multidisciplinarity; Medieval Age; Textual serie; Historiografía lingüística; Inter- y multidisciplinariedad; Edad Media; Series textuales; https://purl.org/pe-repo/ocde/ford#6.02.06